Screening of blending soybean oil with waste cooking oil for biolubricant precursor - Mohd Juhayry Mohd Hayat (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
During recent years the interest in environment friendly and readily biodegradable lubricant based on vegetable oil has increased. So, in this study, soybean oil (SO) was blended with waste cooking oil (WCO) and three parameters were screened in this experiment which are agitation speed, blending time and oil ratio. The aim was to obtain the higher percentage of oleic acid in blending oil. Before blending, the percentage of oleic acid in WCO was 23.72 % and SO was 21.3 %. After blending process, it was observed that the highest percentage of oleic acid obtained was 31.2% while the lowest percentage was 22.15 %. The screening process was done using Design of Experiment (DOE) software. From ANOVA analysis, it can be concluded that oil ratio, blending time and interaction between oil ratio and agitation speed gave significant effect for the percentage of oleic acid in blending oil. As for physicochemical properties, there were three analysis that were done before and after blending, peroxide value (PV) for SO is 2.16 meq/kg, WCO oil is 7.48 meq/kg while after blend highest PV obtained was 7.5 meq/kg and the lowest was 3.63 meq/kg. For acid value (AV) before blend, AV for SO was 0.5799 mg KOH/g and for WCO was 0.6875 mg KOH/g while after blend, the highest AV was 0.6827 mg KOH/g while the lowest was 0.5985 mg KOH/g. The last physicochemical analysis was saponification value (SV), before blend SV for SO was 181.72 mg KOH/g and for WCO was 192.98 mg KOH/g while after blend, the highest SV obtained was 188.9518 mg KOH/g while the lowest was 183.2563 mg KOH/g. So, it can be concluded that by blending WCO and SO can increase the percentage of oleic acid content and improve the characteristic of the new blended oil as a precursor of biolubricant.